Caste-based Transformation in Dalit Community: A Narrative Inquiry - Khatiwada, Thamindra (Patan Pragya, 2022)
This article attempts to explore the way of caste-based transformation in Mudkhu of Tarkeshwor Municipality in Kathmandu. The method was developed with interpretive research paradigm as narratives had immeasurable potentialities to construct meaning of socio-cultural situations of Dalits’ lives and caste-based transformation. I, as narrative inquirer, studied the Dalit based caste transformation on occupation, educational system and cultural practices. Caste-based discrimination was severely practiced in society in the past. However, it is decreasing day by day at present. Due to various reasons and efforts flexibility is being taken places against caste-based discrimination in the society. It is, perhaps, because of transformative educational system, in the recent decades, the structure and the functioning of the caste system and its economic and social aspects are greatly changing. The rigidities of the caste system are changing. Education is one of the best means to address Dalit issue with the advocacy of equality and equity. All these restrictive measures have been changed. Education, awareness and modernization are the best means to address Dalit issue with the equality and equity.